The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fpsyg.2021.724022
|View full text |Cite
|
Sign up to set email alerts
|

“Brain Fog” by COVID-19 or Alzheimer’s Disease? A Case Report

Abstract: Cognitive symptoms after COVID-19 have been increasingly recognized several months after the acute infection and have been designated as “brain fog.” We report a patient with cognitive symptoms that started immediately after COVID-19, in which cerebrospinal fluid biomarkers were highly suggestive of Alzheimer’s disease. Our case highlights the need to examine patients with cognitive symptoms following COVID-19 comprehensively. A detailed assessment combining clinical, cognitive, and biomarker studies may help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Patients with Parkinson’s disease (PD) showed worsened motor and nonmotor symptoms after being diagnosed with COVID-19 [ 22 ]. Meanwhile, several case reports described the development of acute parkinsonism, AD, or amyotrophic lateral sclerosis (ALS) following COVID-19 [ 23 25 ]. However, the observational studies might be biased by unavoidable confounding factors, and cannot determine causation.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Parkinson’s disease (PD) showed worsened motor and nonmotor symptoms after being diagnosed with COVID-19 [ 22 ]. Meanwhile, several case reports described the development of acute parkinsonism, AD, or amyotrophic lateral sclerosis (ALS) following COVID-19 [ 23 25 ]. However, the observational studies might be biased by unavoidable confounding factors, and cannot determine causation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our results indicated that AD has the highest number of overlapping GO biological processes (COVID-19 ∩ Disease) that can be modulated by SARS-CoV-2 through virus–host PPIs, whereas Epilepsy has the lowest number of overlapping processes, Figure 3 A. Cognitive symptoms, such as memory impairment and brain fog, are commonly reported after COVID-19 and memory problems are also a major symptom of AD [ 71 , 72 , 109 ]. A recent case study has shown that a patient that had cognitive symptoms after COVID-19 had increased CSF biomarkers associated with AD [ 110 ]. In addition, elevated levels of serum neurodegenerative biomarkers similarly to those observed in AD have been found in hospitalized COVID-19 patients [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this supports the consistency of the cognitive impairment post-COVID syndrome, which has a relatively characteristic cognitive profile characterized by attention/processing speed deficits with or without associated episodic memory and executive function deficits. This has important implications for the differential diagnosis because the identification of patients after COVID-19 displaying other cognitive profiles with a predominant impairment of other cognitive domains beyond attention/processing speed (e.g., visuospatial, language) should suggest alternative diagnoses [19]. On the other hand, clustering analysis may be helpful in determining the optimal cutoff points for patient classification following an unsupervised strategy.…”
Section: Discussionmentioning
confidence: 99%